Identification and characterization of four Drosophila suzukii cellularization genes and their promoters - Yan, Ying; Jaffri, Syeda A.; Schwirz, Jonas; Stein, Carl; Schetelig, Marc F. (BMC genetics, 2020)
The spotted-wing Drosophila (Drosophila suzukii) is a widespread invasive pest that causes severe economic damage to fruit crops. The early development of D. suzukii is similar to that of other Drosophilids, but the roles of individual genes must be confirmed experimentally. Cellularization genes coordinate the onset of cell division as soon as the invagination of membranes starts around the nuclei in the syncytial blastoderm. The promoters of these genes have been used in genetic pest-control systems to express transgenes that confer embryonic lethality. Such systems could be helpful in sterile insect technique applications to ensure that sterility (bi-sex embryonic lethality) or sexing (female-specific embryonic lethality) can be achieved during mass rearing. The activity of cellularization gene promoters during embryogenesis controls the timing and dose of the lethal gene product. Here, we report the isolation of the D. suzukii cellularization genes nullo, serendipity-α, bottleneck and slow-as-molasses from a laboratory strain. Conserved motifs were identified by comparing the encoded proteins with orthologs from other Drosophilids. Expression profiling confirmed that all four are zygotic genes that are strongly expressed at the early blastoderm stage. The 5' flanking regions from these cellularization genes were isolated, incorporated into piggyBac vectors and compared in vitro for the promoter activities. The Dsnullo promoter showed the highest activity in the cell culture assays using D. melanogaster S2 cells. The similarities in the gene coding and 5' flanking sequence as well as in the expression pattern of the four cellularization genes between D. melanogaster and D. suzukii, suggest that conserved functions may be involved in both species. The high expression level at the early blastoderm stage of the four cellularization genes were confirmed, thus their promoters can be considered in embryonic lethality systems. While the Dsnullo promoter could be a suitable candidate, all reported promoters here are subject to further in vivo analyses before constructing potential pest control systems.